2013
DOI: 10.3389/fgene.2013.00104
|View full text |Cite
|
Sign up to set email alerts
|

The UGT1A6_19_GG genotype is a breast cancer risk factor

Abstract: Validation of an association between the UGT1A6_19_T>G (rs6759892) polymorphism and overall breast cancer risk. A pilot study included two population-based case-control studies from Germany (MARIE-GENICA). An independent validation study comprised four independent breast cancer case-control studies from Finland (KBCP, OBCS), Germany (BBCC), and Sweden (SASBAC). The pooled analysis included 7418 cases and 8720 controls from all six studies. Participants were of European descent. Genotyping was done by MALDI-TOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“… 38 It has been indicated that the GG genotype can decrease UGT1A6 activity 21 and may render individuals more susceptible to the development of breast cancer. 39 In the present study, no significant association between the GG or AG genotypes of the UGT1A6 rs2070959 and HBV infection was observed in the three groups. For the AA genotype, however, increased frequencies were associated with HBV infection in all three ethnic groups.…”
Section: Discussioncontrasting
confidence: 65%
“… 38 It has been indicated that the GG genotype can decrease UGT1A6 activity 21 and may render individuals more susceptible to the development of breast cancer. 39 In the present study, no significant association between the GG or AG genotypes of the UGT1A6 rs2070959 and HBV infection was observed in the three groups. For the AA genotype, however, increased frequencies were associated with HBV infection in all three ethnic groups.…”
Section: Discussioncontrasting
confidence: 65%
“…These findings suggest that polymorphisms in UGT1A4 (rs11673726), UGT1A6 (rs6759892) and UGT1A8 (rs10167119) may be of clinical significance, as they may play a role in the levels of bioavailable estradiol and estrone in postmenopausal women. Although previous studies have reported increased risk of breast cancer in those carrying the GG genotype of UGT1A6 (rs6759892) [ 10 11 ], future studies are needed to confirm the clinical significance of these findings and whether or not genetic polymorphisms in UGT1A4 (rs11673726) and UGT1A8 (rs10167119) are also associated with increased risk of breast cancer in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…UGT family members play an important role in the development of breast cancer. The UGT1A6 gene polymorphism is associated with breast carcinogenesis in the European population, and people with the UGT1A6-19-GC genotype have an increased risk of developing breast cancer ( 24 ). Furthermore, the UGT1A8 polymorphism is associated with breast cancer and leads to an increased risk of breast cancer cell malignancy ( 25 ).…”
Section: Roles Of Ugts In Tumorsmentioning
confidence: 99%